A Comprehensive Approach for India’s Water Resources Development - Sharma, Dinesh C (Annals of Arid Zone, 2016)
For a nation which derives more than half of its national income from agriculture and allied activities, water resources planning and management plays a decisive role. India has, suffered a serious economic setback due to severe droughts in recent years. A review of the nation’s natural condition’s irrigation facilities is Summarized,and an approach for comprehensive planning of the nation’s water resources agency and regional study centers. The importance of integrated approach for developing surface as well as ground water is recognized for optimal development, with more emphasis laid on ground water since its late recognition.